Model Biorekognisi Pengenalan Salmonella typhi Pada Biosensor Elektrokimia - Cusiyani Aprillia; Salma Tajki Mulkiyah (Jurnal Biodiversitas dan Bioteknologi, 2024)
Typhoid fever is a significant health issue in Indonesia, particularly among children aged 5–14 years, with a prevalence rate of 1.60% of the total population. This disease is caused by Salmonella typhi, a pathogenic bacterium with high virulence and resistance levels. Delayed diagnosis and treatment increase the risk of mortality to 5–6%. Therefore, a sensitive, rapid, and accurate diagnostic tool is urgently needed to detect this bacterium. This research uses a literature review method by analyzing 32 journals that discuss the detection of S. typhi bacteria using biosensors. These journals were obtained from Google, PubMed, and Google Scholar, and selected based on criteria such as year of publication, relevance, scope, journal reputation, and author credibility. Recent scientific articles discussing various bioreceptors, such as antibodies, DNA probes, and aptamers. Electrochemical biosensors were selected due to their advantages in sensitivity, selectivity, cost-efficiency, and on-site detection capabilities. The results indicate that aptamers show the greatest potential as bioreceptors compared to antibodies and DNA probes. Aptamers offer high affinity, stability under extreme conditions, and low production costs. With a sensitivity of up to 10 fM and high selectivity, aptamers are an innovative solution for improving the accuracy and speed of S. typhi detection. In conclusion, electrochemical biosensors based on aptamers represent a promising technology for detecting S. typhi, which is expected to reduce mortality rates from typhoid fever through more effective early diagnosis.